TRADE DYNAMICS ON THE BARITO RIVER - Akbar, Wahyu; Ara, Alvarenza Willy (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
The Barito River plays a crucial role in the economic dynamics of Central and South Kalimantan. From the era of ancient kingdoms to modern times, it has been a key trade and social route, connecting inland areas with the international port of Banjarmasin. As early as the 8th century, the Barito River was involved in trade, particularly with the arrival of Muslim traders from Java, Sumatra, Johor, Gujarat, and China. The Dutch colonial era brought significant changes, including trade monopolies and political influences that restricted the freedom of local traders. In modern times, infrastructure and transport development along the river has boosted trade activities, especially for commodities like palm oil, coal, and timber. The research methodology employed is literature review, collecting data from various sources. The findings indicate that trade on the Barito River has not only impacted economic development but has also brought significant social and cultural changes to the local community. The floating market, a local tradition, has been eroded by modernization but remains an important part of Banjar culture. This study explores the long history and trade dynamics of the Barito River, revealing its vital role in local life and providing insights into the future of trade in the region. Despite challenges from modernization and social changes, the Barito River continues to be a vital transportation route for the local community.